The reed cutter and Captain Shigemoto's mother two novellas - Tanizaki, Junʼichirō 1886-1965 (Knopf, 1994)
The Reed Cutter has a contemporary setting, though it might have taken place any film in the past thousand years. On a fine September evening, the narrator decides to make a solitary excursion to the site of an ancient imperial palace south of Kyoto, a place now lost and overgrown near the banks of a river. Musing upon old poems, passages of history and topographical antiquities, he eventually finds himself among the reeds of a sandbar sipping sake from the bottle he has brought with him, watching the moon rise over the river, and scribbling bits of verse in his notebook. Suddenly he is surprised to discover that he is not alone. A strange man joins him and begins to tell a most extraordinary tale about his father, about a scene glimpsed in a moonlit garden forty years before, and about a mysterious woman who has become a lasting obsession